2022
DOI: 10.3389/fcimb.2022.877643
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application Evaluation of Elecsys® HIV Duo Assay in Southwest China

Abstract: BackgroundHIV/AIDS continues to be a serious health concern of morbidity and mortality globally, and novel HIV testing is still an important component of diagnosing HIV earlier and reducing the spread of HIV. The Elecsys® HIV Duo assay is a 4th generation assay that can detect both HIV-1 p24 antigen (Ag) and HIV-1/2 antibody (Ab) in parallel and show the subresults for the Ab and Ab units.ObjectivesTo evaluate the clinical performance of the Elecsys® HIV Duo assay on the new cobas E 801 analyzer using a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Yang et al recently published results of an HIV screening program using the same Roche assay and analyzer that we used. They reported that of the 578 participants who screened with a positive HIV result, 13.3% were both Ag and Ab positive, 77.7% were Ab only positive, and 9.0% were Ag only positive [ 13 ]. The authors are not aware of similar behavior in other serology assays in concurrent viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al recently published results of an HIV screening program using the same Roche assay and analyzer that we used. They reported that of the 578 participants who screened with a positive HIV result, 13.3% were both Ag and Ab positive, 77.7% were Ab only positive, and 9.0% were Ag only positive [ 13 ]. The authors are not aware of similar behavior in other serology assays in concurrent viral infections.…”
Section: Discussionmentioning
confidence: 99%